Pharisaicus hydrops. Łk 14,2-4 w przepowiadaniu Piotra Chryzologa - Paczkowski, Mieczysław (Vox Patrum, 2023)
The biblical texts indubitably shaped the content of the sermons of Peter Chrysologus. He delivered sermons on the Gospel of St. Luke. The lecture on the healing of the man with dropsy (Luke 14:2-4) appears in Sermo 99 bis. The homily has a polemical resonance, but it concerns the situation described in the evangelic text. It is elaborated under a rhetorical and theological aspect. The bishop of Ravenna emphasized the symbolic and moral value of illness. The preacher used the appropriate means to arouse the desired response from the audience and to transmit the spiritual and moral teaching. The homily in question, like other speeches, abandoned rhetorical figures and realistic comparisons.